Magnetic resonance imaging assessed cortical porosity is highly correlated with μCT porosity - Bae, Won C (2014)
Cortical bone is typically regarded as “MR invisible” with conventional clinical magnetic resonance imaging (MRI) pulse sequences. However, recent studies have demonstrated that free water in the microscopic pores of cortical bone has a short T2* but a relatively long T2, and may be detectable with conventional clinical spin echo (SE) or fast spin echo (FSE) sequences. In this study we describe the use of a conventional two-dimensional (2D) FSE sequence to assess cortical bone microstructure and measure cortical porosity using a clinical 3T scanner. Twelve cadaveric human cortical bone samples were studied with MRI and micro computed tomography (μCT) (downsampled to the same spatial resolution). Preliminary results show that FSE-determined porosity is highly correlated (R(2) = 0.83; P < 0.0001) with μCT porosity. Bland Altman analysis suggested a good agreement between FSE and μCT with tight limit of agreement at around 3%. There is also a small bias of -2% for the FSE data, which suggested that the FSE approach slightly underestimated μCT porosity. The results demonstrate that cortical porosity can be directly assessed using conventional clinical FSE sequences. The clinical feasibility of this approach was also demonstrated on six healthy volunteers using 2D FSE sequences as well as 2D ultrashort echo time (UTE) sequences with a minimal echo time (TE) of 8 μs, which provide high contrast imaging of cortical bone in vivo.